2019
DOI: 10.1177/2280800019851771
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of endodontic sealers and medications containing chitosan and silver nanoparticles against Enterococcus faecalis

Abstract: Background: The main microorganism associated with the failure of endodontic treatments is Enterococcus faecalis. Although several endodontic therapeutics have demonstrated antimicrobial activity against E. faecalis, the antimicrobial effectiveness of chitosan (CsNPs) and silver nanoparticles (AgNPs) included into conventional endodontic sealers for endodontic therapies is still unclear. Aim: The objective of this study was to evaluate the antibacterial activity increment (AAI) of endodontic sealers containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
(73 reference statements)
0
24
0
Order By: Relevance
“…In addition, several recent reports demonstrated that chitosan-based scaffolds promoted the proliferation, migration, and odontoblastic differentiation of dental pulp stem cells and mesenchymal stem cells both in vitro and in vivo [146,147,148,149] (Table 2). The use of chitosan as a vector for antimicrobials has also been tested with interesting outcomes [150].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, several recent reports demonstrated that chitosan-based scaffolds promoted the proliferation, migration, and odontoblastic differentiation of dental pulp stem cells and mesenchymal stem cells both in vitro and in vivo [146,147,148,149] (Table 2). The use of chitosan as a vector for antimicrobials has also been tested with interesting outcomes [150].…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that chitosan combined with 2% chlorhexidine gel showed very good destructive effects against E. faecalis in root canals [54]. This mixture also works well as a root canal sealer [55].…”
Section: Chitosan Nanoparticlesmentioning
confidence: 89%
“…The use of nanomaterials-due to their small particle size-also potentially offers a large surface area/mass ratio and an increase in chemical reactivity when compared to its correspondent original material [41]. The addition of nanoparticles to endodontic cements has increased the antimicrobial activity inside dentinal tubules and the consistency of the materials [42,43]. Chlorhexidine is an example of a substance used in its nanoparticulated form in endodontic cements, offering broad-spectrum antimicrobial action, which makes it effective against Gram-positive bacteria, Gram-negative bacteria, and fungi [29].…”
Section: Root Canal Filling Materials (Sealers)mentioning
confidence: 99%